2005
DOI: 10.1080/15287390590895054
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Activity of Cosmetic Components in Reporter Cell Lines: Parabens, UV Screens, and Musks

Abstract: In this work, the estrogenic effects of three classes of substances included in cosmetic formulations-parabens, ultraviolet (UV) screens, and musk fragrances-were studied. Their estrogenic activity was measured with the use of three reporter cell lines: HELN, HELN ERalpha, and HELN ERbeta. These three cell lines allowed for the measurement of estrogenic activity toward estrogen receptors alpha and beta (ERalpha and ERbeta, while taking nonspecific interactions into account. Eight of the 15 substances tested sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(83 citation statements)
references
References 22 publications
2
78
0
2
Order By: Relevance
“…Furthermore, ERβ is now known to act as a growth inhibitor and the relative proportion of ERβ in breast cancer cells is thought to in½uence the outcome in breast cancer (Speirs et al, 2004), which suggests that altering ERβ actions could be as detremental as enhancing ERα activity. Recent work has suggested that individual parabens may vary in their relative binding af¼nity for ERα and ERβ (Okubo et al, 2001;Gomez et al, 2005), which in turn suggests that there could be equally varied responses of the different parabens in different tissues and during development of different breast cancers. Whether the parabens can also bind to the oestrogen-related receptors will also be important in the light of the recent description of the binding of bisphenol A to human oestrogen-related receptor-γ (Okada et al, 2008).…”
Section: Role Of Era and Erbmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, ERβ is now known to act as a growth inhibitor and the relative proportion of ERβ in breast cancer cells is thought to in½uence the outcome in breast cancer (Speirs et al, 2004), which suggests that altering ERβ actions could be as detremental as enhancing ERα activity. Recent work has suggested that individual parabens may vary in their relative binding af¼nity for ERα and ERβ (Okubo et al, 2001;Gomez et al, 2005), which in turn suggests that there could be equally varied responses of the different parabens in different tissues and during development of different breast cancers. Whether the parabens can also bind to the oestrogen-related receptors will also be important in the light of the recent description of the binding of bisphenol A to human oestrogen-related receptor-γ (Okada et al, 2008).…”
Section: Role Of Era and Erbmentioning
confidence: 99%
“…The discovery that ERβ immunoreactivity was increased in severely dysplastic nevi and lentigo malignas (in-situ melanoma) but decreased in melanomas progressively deeper in the dermis suggests that ERβ may be playing a role in the biology of these cancers and might serve as a useful prognostic marker (Schmidt et al, 2006). In the light of an involvement of ERβ on melanocytic pathophysiology (Schmidt et al, 2006), the ability of methylparaben to potentiate UV-induced damage in keratinocytes (Handa et al, 2006) and the ability of parabens to act via ERβ (Okubo et al, 2001;Gomez et al, 2005), a potential involvement of parabens (alone or together with other oestrogenic chemicals in cosmetics including UV ¼lters) should now be considered in studies of the development of malignant melanoma. The higher rate of melanoma in younger people (Gavin and Walsh, 2005;Strouse et al, 2005;Downard et al, 2007), the increasing incidence in youth (Strouse et al, 2005;Downard et al, 2007) and the inverse relationship with social deprivation (Gavin and Walsh, 2005) could all correlate with greater use of paraben-containing skincare/suncare products, be it through more lavish amounts at each application, more frequent applications or a lifestyle where products are required more often and at higher levels.…”
Section: Parabens and Skin Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Parabens have estrogen-like properties in cell cultures, causing proliferation of estrogen-responsive cells, although they are thousands of times less potent than naturally-occurring estrogen in this regard [164][165][166]. Parabens were found to activate both estrogen receptors, ER-α and ER-β, with similar or stronger effect versus ER-β receptors [165,167,168]. The ability of parabens to transactivate the ER in vitro increases with alkyl tail bulkiness [166].…”
Section: Parabensmentioning
confidence: 99%